(untitled) (Baghdad Science Journal, 2005)
The dental amalgam of radioactive materials in the restoration of teeth because of its readily adaptable to existing materials in the oral cavity in addition to mechanical properties such as hardness mechanical resistance Alndgat and others in this study were prepared Almlagm used Guy dental restoration of silver alloy tin plus some elements to improve the characteristicsmechanical such as copper, zinc or indium in addition to mercury